Cumulative exposure to dust causes accelerated decline in lung function in tunnel workers. Issue 10 (1st October 2001) - Ulvestad, B; Bakke, B; Eduard, W; Kongerud, J; Lund, M B
Abstract : OBJECTIVES: To examine whether underground construction workers exposed to tunnelling pollutants over a follow up period of 8 years have an increased risk of decline in lung function and respiratory symptoms compared with reference subjects working outside the tunnel atmosphere, and relate the findings to job groups and cumulative exposure to dust and gases. METHODS: 96 Tunnel workers and a reference group of 249 other heavy construction workers were examined in 1991 and re-examined in 1999. Exposure measurements were carried out to estimate personal cumulative exposure to total dust, respirable dust, α-quartz, oil mist, and nitrogen dioxide. The subjects answered a questionnaire on respiratory symptoms and smoking habits, performed spirometry, and had chest radiographs taken. Radiological signs of silicosis were evaluated (International Labour Organisation (ILO) classification). Atopy was determined by a multiple radioallergosorbent test (RAST). RESULTS: The mean exposure to respirable dust and α-quartz in tunnel workers varied from 1.2–3.6 mg/m 3 (respirable dust) and 0.019–0.044 mg/m 3 (α-quartz) depending on job task performed. Decrease in forced expiratory volume in 1 second (FEV1 ) was associated with cumulative exposure to respirable dust (p<0.001) and α-quartz (p=0.02). The multiple regression model predicted that in a worker 40 years of age, the annual decrease in FEV1 would be 25 ml in a non-exposed non-smoker, 35 ml in a non-exposed smoker, and 50–63 ml in a non-smoking tunnel worker (depending on job). Compared with the reference group the odds ratio for the occurrence of new respiratory symptoms during the follow up period was increased in the tunnel workers and associated with cumulative exposure to respirable dust. CONCLUSIONS: Cumulative exposures to respirable dust and α-quartz are the most important risk factors for airflow limitation in underground heavy construction workers, and cumulative exposure to respirable dust is the most important risk factor for respiratory symptoms. The finding of accelerated decline in lung function in tunnel workers suggests that better control of exposures is needed.